The Power of Connections: AAP COVID-19 ECHO Accelerates Responses During a Public Health Emergency. Issue 1 (January 2022) - Bernstein, Henry H.; Calabrese, Trisha; Corcoran, Peter; Flint, Laurence E.; Munoz, Flor M.
Abstract : Context: Pediatric providers across the United States have sought guidance on how to care for the nation's children during the uncertain historic times of the COVID-19 pandemic. The health care community has been challenged by the unprecedented burden of caring for patients when they have evolving guidelines and limited information about the effects of the virus on children. Program: In response, the American Academy of Pediatrics (AAP) rapidly launched a national initiative to increase child health professionals' knowledge, skills, and self-efficacy. This COVID-19 ECHO (E xtension for C ommunity H ealthcare O utcomes) program created communities of learners among child health professionals and subject matter expert faculty using didactic and case-based presentations that foster an "all-teach, all-learn" approach. Implementation: The initial AAP COVID-19 ECHO program hosted more than 900 participants in 127 individual virtual sessions, with approximately 25 participants per session. The evolving nature of the pandemic necessitated dynamic and continuous bidirectional flow of concerns and information relevant to participants. Session topics were selected in a "just-in-time" fashion based on participant feedback from the prospective postsession surveys and faculty recommendations; speakers brought data and expert recommendations. Evaluation: To assess impact, the AAP used a mixed-methods approach to evaluate the program's effectiveness in meeting its educational objectives. The 2-phase evaluation collected quantitative and qualitative data through an integrated feedback structure that utilized prospective postsession and retrospective postprogram surveys, along with postprogram focus groups. Discussion: As the COVID-19 pandemic surges and another influenza season is upon us, the ECHO model is an effective strategy for facilitating bidirectional communication and education to build child health professionals' knowledge, skills, and self-efficacy during an unprecedented and ongoing public health emergency. Key Points: The ECHO model is an effective strategy for health care organizations to facilitate bidirectional communication and education in building health professionals' clinical knowledge, skills, and self-efficacy during the unprecedented and ongoing public health emergency of the COVID-19 pandemic.